Assessing the effect of government surveillance on firm supererogation: The case of the U.S. automobile industry. (4th January 2018) - Cavazos, David E.; Rutherford, Matthew; Berman, Shawn L.
Abstract : This study builds on prior research investigating the antecedents of firm supererogation. Examining vehicle recalls in the U.S. automobile industry from 1966 to 2010 reveals that surveillance‐based government enforcement programs can have widespread industry effects on a specific type of supererogatory action, firm volunteerism. Specifically, increases in government surveillance are associated with firms going beyond what is legally required of them by initiating voluntary product recalls for defects not covered in existing government regulation. Such effects are shown to be unique among surveillance efforts as other government enforcement activities, such as standards‐based regulation, are revealed to have a negative association with firm supererogation.